Analisis Etika Dalam Interaksi Sosial Mahasiswa: Nur Intan Nirwang, A Nurul Mutmainnah - Nur Intan Nirwangi; A Nurul Mutmainnah (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2023)
This study will explain the analysis of student social interaction by providing several questions including asking about senior level interactions between junior levels. The method in our research used a qualitative approach, in this case in-depth interviews. The purpose of this in-depth discussion is for us to take an approach so that we can find out how the seniors think about their juniors and vice versa. In a senior and junior socialization cycle, we are familiar with it because basically there are senior and junior cycles that can be said to be beneficial and detrimental, besides that in the senior-junior cycle, juniors will definitely provide learning from their seniors which will add insight to the seniors and juniors. his junior. Being a senior is basically not easy because one of the roles as a senior is to be an example for juniors and mentors in things that are not yet known by their juniors. Besides that, not only knowledge but in speech and ethics are important things that need to be shot because when juniors don't have ethics and say the wrong words, juniors will follow and apply.